Impact of EEDI on Ship Design and Hydrodynamics A Study of the Energy Efficiency Design Index and Other Related Emission Control Indexes - Hasan, S. M. Rashidul (My University, 2011)
Around 90% of global trade is carried by sea1 due to the reason that it is the most economical and fuel efficient mode of cargo transportation. The total trade volume is increasing throughout the last century for the same reason. On the other hand according to the Green House Gas study by IMO, International Maritime Organization in 2000, ships engaged in international trade in 1996 contributed about 1.8% of the total world’s CO2 emissions which is approximated as 2.7% in 20072. At the present trend, this percentage could go two or three times higher from the present by 20503. In order to control this CO2 emission from shipping, IMO has developed the first ever global CO2 reduction index in the world, known as EEDI, Energy Efficiency Design Index. The basic formulation of EEDI is based on the ratio of total CO2 emission per tonne.mile. As CO2 depends upon fuel consumption and fuel consumption depends upon the total power requirements, eventually this EEDI formulation has certain impact on ship design parameters and hydrodynamics. At this point SSPA Sweden AB4 wanted to have an in depth knowledge about the background of EEDI, other indexes (except EEDI) for reducing CO2 emission developed by other organizations, formulations of different indexes and working method, impact of EEDI on ship design and the hydrodynamics. In order to find the impact on ship design and hydrodynamics, parametric analyses of ship is accomplished for different ship types such as Bulk Carrier, Tanker, Container vessel etc. A simple tool has been developed to calculate resistance and power with Holtrop & Mennen, 1982 method. Using the tool the main engine power is predicted after calculating the resistance and finally EEDI is calculated with the current IMO formulation. Finally, the results are presented as the effect on EEDI and hydrodynamics by changing ship design parameters such as Length, Beam, Draft, Prismatic Coefficient, Block Coefficient and suggestions have been made in order to achieve the required EEDI. An effort was also made to analyse the criticism against the present EEDI formulation, guideline and reference line, as it is quite a heavy debate now, whether this implementation will really reduce the CO2 emission or not.
Keywords: Farkostteknik; Transport; Vehicle Engineering; Transport